2011
DOI: 10.3233/jad-2010-100156
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Cerebral Correlates of CERAD Test Performance in Mild Cognitive Impairment and Alzheimer's Disease

Abstract: The objective of this study was to investigate the association between structural cerebral changes and neuropsychological deficits in mild cognitive impairment (MCI) and Alzheimer's disease (AD). Sixty patients with MCI, 34 patients with mild to moderate AD, and 32 healthy controls underwent both extensive neuropsychological assessment (CERAD test battery) and high-resolution structural magnetic resonance imaging. We used optimized voxel based morphometry to investigate (i) differences in gray matter density b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 41 publications
6
36
0
Order By: Relevance
“…They suggested that depression patients might compensate for their dysfunctional prefrontal 'search' mechanisms by using more direct strategies to obtain entrance to their verbal hippocampal memory systems. In addition, significant correlations between the hippocampal volumes and semantic fluency task were observed in the patients with MCI and AD (Dos Santos et al, 2011;Gleissner and Elger, 2001). A previous voxel-based lesion symptom mapping study on the stroke patients showed that the scores of semantic fluency task were correlated with the putamen and the insula (Baldo et al, 2006).…”
Section: Correlation Analyses With Clinical Outcomes and Neuropsycholmentioning
confidence: 93%
“…They suggested that depression patients might compensate for their dysfunctional prefrontal 'search' mechanisms by using more direct strategies to obtain entrance to their verbal hippocampal memory systems. In addition, significant correlations between the hippocampal volumes and semantic fluency task were observed in the patients with MCI and AD (Dos Santos et al, 2011;Gleissner and Elger, 2001). A previous voxel-based lesion symptom mapping study on the stroke patients showed that the scores of semantic fluency task were correlated with the putamen and the insula (Baldo et al, 2006).…”
Section: Correlation Analyses With Clinical Outcomes and Neuropsycholmentioning
confidence: 93%
“…Subjects were categorized based on K-MMSE score (less than 20 for AD, between 20 and 25 for MCI, and greater than 25 for the control group) [18]. After screening test, we also evaluated their cognitive function using the K-CERAD, which assesses verbal fluency, naming, immediate/delayed recall, constructional praxis, and constructional praxis recall, and this measure was also used to identify AD or MCI in dividing line patients, such as K-MMSE score 20 or 25 [5]. Those subjects were further categorized into each group based on K-CERAD score: one item failure MCI group, and more than two item failures AD group.…”
Section: Subjects Classificationmentioning
confidence: 99%
“…Declarative memory deficits involving verbal memory and LM constitute the hallmark of MCI and AD [12,46] and were demonstrated in the vast majority of patients with MCI and all patients with manifest AD who showed significant deficits in LM (81.5 and 100%) and verbal memory (84.7 and 100%), respectively. As described in a wealth of studies, these deficits refer to changes of the hippocampus and other structures of the medial temporal lobe, which can already be demonstrated in MCI and early AD [47], as cited in Schröder and Pantel [1].…”
Section: Discussionmentioning
confidence: 99%
“…A much higher frequency was established for the multiple-domain amnestic subtypes, mainly due to the high frequency of executive deficits [11]. This is of particular importance as the latter can be referred to the frontal cortices, which are generally assumed not to be primarily involved in AD [12,13]. …”
Section: Introductionmentioning
confidence: 99%